Forwards or backwards—regulatory focus orientation of offense and defense players in team sports - Kritzler, S.; Best, A.-L.; Terwiel, S. (International Journal of Sport and Exercise Psychology, 2023)
Playing positions in team sports can be divided into two broad categories: offense players who typically prioritise scoring points over preventing the other team from scoring and defense players who typically prioritise preventing the opponents from scoring over scoring themselves. Thus, offense and defense players have very different approaches and goals within the game. It therefore seems likely that the players of these different positions also differ from each other in relevant motivational or self-regulatory characteristics such as their regulatory focus orientation. Because the definitions of regulatory promotion focus and regulatory prevention focus match very closely the definitions of offense and defense players, we hypothesised that offense players should have higher levels of promotion focus than defense players and that defense players should have higher levels of prevention focus than offense players. Using data from a preregistered large-scale online survey on playing positions and personality in team sports (N = 2,185 athletes from 18 different team sports), we found in linear regression analyses that offense players indeed had significantly higher levels of promotion focus, whereas defense players indeed had significantly higher levels of prevention focus. For prevention focus, these differences were also robust to both a different classification of offense and defense and to the inclusion of moderators. Overall, these findings suggest that regulatory focus may play an important role in team sports. Future research should therefore further examine these effects, their mechanisms, and their consequences in terms of sport satisfaction, performance, and regulatory fit.